2014
DOI: 10.1007/s00170-014-6606-9
|View full text |Cite
|
Sign up to set email alerts
|

Cutting performance and coated tool wear mechanisms in laser-assisted milling K24 nickel-based superalloy

Abstract: Laser-assisted machining (LAM) offers the ability to machine superalloys more efficiently and economically by providing the local heating of the workpiece prior to material removed by traditional cutting tool. The effectiveness of LAM was studied by measuring the cutting forces, surface roughness, and tool wear under various material removal temperatures (Tmr). It is demonstrated by an appropriate 30-70 % decrease in cutting force, an obvious reduction in the surface roughness, and an appropriate 46 % increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…They claimed that the use of cryogenic cooling resulted in improving tool life but did not result in a reduction in forces. Kong et al [12] studied the effect of workpiece heating instead of cooling on machinability and showed that laser heating during milling of a Ni-based alloy significantly reduced VB and various force values. However, despite of the well-recognised importance of forces and the progression of tool deterioration as parts of the assessment of machinability, more closely correlating the two was not attempted in these two studies of investigating the effect of thermal condition during milling on machinability.…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that the use of cryogenic cooling resulted in improving tool life but did not result in a reduction in forces. Kong et al [12] studied the effect of workpiece heating instead of cooling on machinability and showed that laser heating during milling of a Ni-based alloy significantly reduced VB and various force values. However, despite of the well-recognised importance of forces and the progression of tool deterioration as parts of the assessment of machinability, more closely correlating the two was not attempted in these two studies of investigating the effect of thermal condition during milling on machinability.…”
Section: Introductionmentioning
confidence: 99%
“…Novak et al [11] noticed several advantages of PEM over conventional machining, including improvement of surface roughness, lower cutting forces, and extended tool life. Kong et al [12] carried out the experiments to evaluate the wear behavior of different commercially available coated tools with preheat technology. Vagnorius [13] showed that, when used properly, high-pressure cooling can help to increase the productivity in machining of heat-resistant alloys with ceramic tools.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the LAMM recorded the lowest value of force components at all tested conditions. Kong et al [34] reported that laser-assisted machining successfully demonstrated the reduction of cutting force by around 30%-70% over the conventional machining process. Because the heat generated by cutting and the lasers approached the melting point, and thus reduced the shear resistances.…”
Section: Cutting Forcementioning
confidence: 99%
“…However, Kong et al [34] investigated the effectiveness of coating material on laser-assisted milling of K24 nickel-based alloy. The amounts of average flank wear increases for both conventional machining and LAM with increasing cutting times are shown in Figure 16.…”
Section: Tool Wearmentioning
confidence: 99%